Using self-determination and expectancy theory to evaluate hybrid learning - Wening Patmi Rahayu; Raya Sulistyowati; Heri Pratikto; Rachmad Hidayat; Bagus Shandy Narmaditya; Zamzani Zainuddin; Siti Zumroh; Rila Ayu Agnes Indarwati (Cogent Education, 2024)
AbstractThis research uses self-determination theory and expectancy theory to investigate how Indonesian students responded to hybrid learning in the post-COVID-19 pandemic. This research specifically examines the impact of instructional support and peer support on academic performance, as well as the role of learning satisfaction as a mediator. Using structural equation modelling, the findings indicate that instructional support has a significant impact on learning satisfaction and academic performance. Indeed, peer support has a significant impact on learning satisfaction and academic performance. Furthermore, learning satisfaction acts as a significant mediator of these indirect effects of these variables on supporting academic performance among Indonesian students. This study also provides implications and contributions of using hybrid learning in promoting academic learning in the post-COVID-19 pandemic.